Effects of fading and interference on system performance in cellular mobile communications - Ye, Song. (2009)
Cellular mobile communication systems will be of increasingly importance in the future. This thesis is concerned with the analysis of interference and fading in such systems. The first emphasis of the study is on the problem of co-channel interference. The co-channel interference effects on the performance of the TDMA/FDMA cellular system in the presence of fast fading are considered. The probabilities of successful transmission and packet loss are derived by taking into account the Rayleigh interference signals as independent fadings, path loss, distance variation, receiver threshold, and carrier-to-interference ratio (C/I). Simulation results are used for verification and comparison. It is found that the analytical results are in good agreement with the simulation results.